Implementation Of Box Behnken Design To Fabricate The Formulation, Optimization And Dissolution Of Blueberry Nanosuspension (Journal of Pharmaceutical Negative Results, 2022)
The present study aims to enhance the bioavailability of Blueberry by formulating it as nanosuspension. Blueberry mainly consists ofanthocyanins which have strong antihyperlipidemic activity but suffers from low bioavailability which causes hindrances in itstherapeutic activity to treat hyperlipidemia. Hence to improve its bioavailability, nanosuspension of blueberry was prepared. BoxBehnken design was applied to predict the effect of independent variables namely concentration of chitosan and concentration oftripolyphosphate (TPP) and stirring speed on two responses namely particle size and entrapment efficiency. The design suggested thata formulation having a particle size of 205.05nm and entrapment efficiency of 76.60 % will be an optimized formulation if it haschitosan, TPP,and stirring speed of 0.5%, 0.05%,and 1050 rpm respectively. The formulation suggested by design was prepared and itwas found that particle size and entrapment efficiency of nanosuspension 198.5 nm and 75.14±0.56 % respectively. In addition, it wasfound to have polydispersity index, refractive index, zeta potential of 0.351, 1.33, 21.08mv respectively.SEM analysis showed thedroplet size under 200nm.When compared towards blueberry nanosuspension with drug extract release it shows the controlled releaseof drug up to 8 hrs which enhances the bioavailability of drug and drug extract suspension showed the maximum release in 2hrs whichshows the immediate release of the drug. As a result, our research shows that nanotechnology might be utilized as an effective approachincreasing the bioavailability of blueberry nanosuspension and this article also focuses on the antihyperlipidemic activity ofanthocyanin.